Personal statement versus psychological test as admission to the nursing degree: an evaluation - Marian Traynor; Colin Mc Neill; Audrey Roulston (BMC, 2022)
Abstract Background A review of admissions to nursing in Northern Ireland was prompted by the growing number of applications and a desire to ensure that the applicants had the right values for a career in nursing. Concerns regarding authorship, plagiarism and reliability of personal statements used to select applicants to interview was the focus of this research. This study evaluates the psychometric properties of a Personal Statement (PS) as a method for admission to a nursing programme and a values-based psychological screening tool, Nurse Match (NM). Methods A self-selecting, purposive sample (n = 228; 9.7%) was drawn from applicants to Schools of Nursing in the United Kingdom (n = 2350). Participants all of whom had completed a Personal Statement were asked to complete a psychological tool and the scoring outcomes and psychometric properties of both tests were investigated. Statistical analysis was conducted using Minitab 17. Results Applicants from 18 schools and five colleges responded. The majority (72.4%) were aged 18-19. Findings provide practical, theoretical, statistical, and qualitative reasons for concluding that the Personal Statement has substantial limitations as a measure of suitability. It does not compare well with international test standards for psychometric tests. In contrast, NM is a valid and reliable measure with good discriminatory power, standardised administration and consistent marking. Conclusion NM is a viable alternative to the PS for shortlisting applicants for nursing interviews.